Alcohol consumption motives and consequences in the South Korean university student culture - Karellos, Alina (2018)
The purpose of the present study is to examine the connection between alcohol and student culture in the Korean university environment. More specifically I aim to shed light on the motives that guide drinking, as well as the social consequences related to it. I will approach the matters through the perspective of social identity theory and aspects of group behavior. In a more general level, the aim of this study is to understand the ways in which alcohol is connected to university environment and group behavior, in order to support the development of new approaches in policies controlling harmful drinking. The research followed a qualitative approach with data collected during a student exchange semester in South Korea, in the latter half of 2017. All together seven semi-structured interviews were collected and analyzed through thematic content analysis. The findings of this study indicate that alcohol consumption is strongly connected to the Korean student culture. Alcohol is used as a medium of bonding and in most socializing events. Its use enhances the sense of collectivism and group homogeneity. The drinking motives that emerged indicate that students participate in drinking activities to achieve a sense of belonging to the group, which will enhance their positive self-concept. Students not participating in drinking activities face negative social consequences that may endanger their position as a group member.